2012
DOI: 10.3402/ljm.v7i0.17251
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of different antidepressants combined with aspirin on thermally induced pain in Albino mice

Abstract: BackgroundCombination analgesics provide more effective pain relief for a broader spectrum of pain. This research examines the possible potentiation of the analgesic effect of different classes of antidepressants when combined with aspirin in thermal model of pain using Albino mice.MethodsDifferent groups of six animals each were injected intraperitoneally by different doses of aspirin (50, 100, or 200 mg/kg), imipramine (2.5, 7.5, 15 or 30 mg/kg), fluoxetine (1.25, 2.5, 5 or 7.5 mg/kg), mirtazapine (1.25, 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is observed for most of the drugs used for analgesia, there is increased response with increase in dose of drugs. [20][21][22][23] Contrary to this, analgesic ceiling effect is the phenomenon that refers to the dose beyond which there is no additional analgesic effect. In a study comparing 400mg versus 600mg of ibuprofen in patients with postoperative dental pain conducted by Seymour and co-workers, showed that there is very little analgesic advantage to doses of ibuprofen above 400mg.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed for most of the drugs used for analgesia, there is increased response with increase in dose of drugs. [20][21][22][23] Contrary to this, analgesic ceiling effect is the phenomenon that refers to the dose beyond which there is no additional analgesic effect. In a study comparing 400mg versus 600mg of ibuprofen in patients with postoperative dental pain conducted by Seymour and co-workers, showed that there is very little analgesic advantage to doses of ibuprofen above 400mg.…”
Section: Discussionmentioning
confidence: 99%
“…Because they are both analgesic and antiinflammatory, the NSAIDs are among the most widely used of all therapeutic classes of drugs. 8 Opioids are the most potent pain-relieving drugs currently available.…”
Section: Neuropathicmentioning
confidence: 99%
“…The specific antidepressant effects are also important alleviating chronic depression is important in helping patients deal more effectively with pain. 8 In spite of having a number of drugs for the management of pain, there is still need for an ideal analgesic agent with favorable safety profile.…”
Section: Neuropathicmentioning
confidence: 99%
“…8 Rheumatoid arthritis, osteoarthritis and musculoskeletal injuries are widely treated with non-steroidal anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%